PTU-171 Recurrence After Successful Radiofrequency Ablation For Barrett's Related Neoplasia Is More Likely In Males: Data From The United Kingdom Patient Registry. (9th June 2014) - Haidry, RJ; Banks, M; Gupta, A; Butt, M; Fullarton, G; Smart, H; Morris, J; Willert, R; Narayanasamy, R; Rodriguez-Justo, M; Novelli, M; Lovat, L
Abstract : Introduction: Barrett's oesophagus (BE) can lead to oesophageal adenocarcinoma (OAC). BE is more prevalent in males. Endoscopic mucosal resection (EMR) for visible lesions followed by Radiofrequency ablation (RFA) have become first line treatment for patients with BE related neoplasia. Recurrence after treatment can occur in up to 25% of patients. Risk factors for recurrence are unclear. Methods: We examine prospective data from United Kingdom (UK) registry of patients undergoing RFA/EMR over past 5 years. We examine if recurrence after treatment is influenced by gender, baseline histology, BE length and prior EMR. Before RFA, visible lesions were removed by EMR. Thereafter patients underwent RFA 3 monthly. Biopsies were taken at 12 months and outcomes for clearance of dysplasia (CR-D) and BE (CR-IM) were assessed. After successful treatment patients were followed up 3 monthly for the first year, 6 monthly for second year and annually thereafter. Biopsies were taken from 1cm below neo z-line and previously treated BE segment. Results: A total of 412 males and 95 females have been treated with no statistical difference in baseline BE length, histology or prior EMR in both groups. CR-D in Males was 84% and CR-IM 80%. In females CR-D was 86% and CR-IM 64% and not significantly different (p = 0.61 and p = 0.22, respectively). Progression to cancer was 3% in both cohorts at 12 months. There were 21 patients from both groups with recurrent dysplasia on follow up biopsy after successful treatment. Median time to recurrence in these after successful RFA was 380 days (IQR 177–615). Twenty recurrences were in males compared to one in female group which was statistically significant (p = 0.04). There were 11 recurrences of IM alone in patients who had confirmed CR-IM at 12 months. All were in male patients (median time to recurrence of 626 days, IQR 237–822). Baseline BE length, histology, prior EMR did not influence risk of recurrence of dysplasia or IM. Conclusion: RFA for BE related neoplasia is equally effective in both males and females. Recurrence of neoplasia after successful eradication although uncommon overall is more common in males. The much lower recurrence rate in women raises the possibility that they could be discharged from follow up after successful treatment or have prolonged surveillance intervals compared to men. This could reduce the burden of surveillance endoscopy on overstretched services. All collaborators of UK RFA registry are acknowledged for their contributions to this work. Disclosure of Interest: None Declared.